PENGENALAN POTENSI FINTECH LENDING DALAM MENDUKUNG PENGEMBANGAN EKONOMI KREATIF DI DESA PEMATANG SERAI, KABUPATEN LANGKAT - Noni Ardian; Pipit Buana Sari; M Chaerul Rizky; Ika Nurhaliza (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2024)
This community service aims to introduce the potential of fintech lending as an innovative financing solution to support the development of the creative economy in Pematang Serai Village, Langkat Regency. The village has significant potential in the creative economy sector; however, limited access to capital is a major barrier to the growth of small and medium enterprises (SMEs) in the area. Fintech lending, as a technology-based lending platform, offers faster and more accessible funding for entrepreneurs. This community service activity includes outreach and education on the concept of fintech lending, its benefits, and how to use it. Additionally, technical training is provided to the villagers and creative business entrepreneurs on how to access and leverage fintech lending platforms. The results of this activity show that the villagers are beginning to understand the importance of fintech lending in supporting their creative businesses, and some entrepreneurs have started applying for financing through these platforms.